Dynamics Relationship Between House Prices And Macroeconomic Aggregates - SABRI, BUKRYMAN (2005)
This study investigates the dynamic relationships amongst the house prices and macroeconomic variables. It is general belief that the macro variables such as inflation rates, industrial production, interest rates and money supply (M2) are some prominent factors to the performance of the house prices. The property market and construction sector are one of the leading indicators for the economic growth.